2018
DOI: 10.1111/lasr.12329
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Legal Mobilization: Perceptions of Justice and the Use of the Tutela in Colombia

Abstract: This article explores the relationship between legal consciousness and legal mobilization in the context of constitutional rights in Colombia. Citizens report extremely low confidence in the state and the judiciary, yet hundreds of thousands of Colombians make constitutional rights claims through the acción de tutela procedure each year. Why does profound skepticism of the ability of the judiciary to provide justice and fair treatment seem to coexist with high levels of use of the legal system? How do perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
0
26
0
2
Order By: Relevance
“…While most of the work discussed to this point has been conducted in the United States and Western Europe, in recent years political scientists have begun to investigate the extent to which these claims hold in other contexts. Examining justice system engagement in non-Western countries and the Global South, these works have found that individuals may turn to the formal legal sphere to resolve disputes and/or claim rights despite deep mistrust of legal institutions (Gallagher, 2006; Hendley, 2012, 2017; Lake et al, 2016; Smulovitz, 2010; Taylor, 2018).…”
Section: Competing Perspectives On Trust and Justice System Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the work discussed to this point has been conducted in the United States and Western Europe, in recent years political scientists have begun to investigate the extent to which these claims hold in other contexts. Examining justice system engagement in non-Western countries and the Global South, these works have found that individuals may turn to the formal legal sphere to resolve disputes and/or claim rights despite deep mistrust of legal institutions (Gallagher, 2006; Hendley, 2012, 2017; Lake et al, 2016; Smulovitz, 2010; Taylor, 2018).…”
Section: Competing Perspectives On Trust and Justice System Engagementmentioning
confidence: 99%
“…In regard to justice institutions, scholars of legal consciousness and mobilization have employed qualitative or mixed methods to explore why people in settings of high institutional mistrust will still turn to the justice system to resolve conflicts, remedy harms, or claim rights. Some offer more rationalist accounts based on need, cost/risk, or expected utility (Hendley, 2012, 2017; Taylor, 2018). Others point to emotional or ideational factors to explain recourse to justice institutions in which people have little faith (e.g., Gallagher, 2006; Lake et al, 2016).…”
mentioning
confidence: 99%
“…1 The role of the Constitutional Court in tutela decisions and interpretation links this case to a broader class of institutional mechanisms at the judiciary's disposal to effect social change by promoting rights in Colombia (Cano-Blandón 2017), in Latin America (Botero 2018), and across the developing world (Rodríguez-Garavito and Rodríguez-Franco 2015). We stress that since its creation three decades ago, the tutela has become a first stop-and perhaps the only stop (Taylor 2018)-for rights protection and integral to Colombia's sociolegal culture. These twin elements grant us significant leverage vis-à-vis the conditions undergirding the public enforcement mechanism thesis.…”
Section: The Colombian Tutelamentioning
confidence: 97%
“…But the tutela itself holds a special significance to Colombians. Taylor's (2018) study of legal consciousness in Colombia suggests that Colombians Perceptions of Protection for Basic Rights, 2004Rights, -2018 Note: Data in the top panels were collected in 2021 online national quota survey administered by Netquest described in Study 3. Temporal series for trust in the judiciary and perceptions that basic rights are protected gathered from the AmericasBarometer.…”
Section: Tutela and Colombia's Sociolegal Culturementioning
confidence: 99%
“…15 As a result, the tutela and the health care system came to be inextricably linked. Furthermore, as noted in Taylor (2018), citizens commonly report that "[u]nfortunately, in Colombia, to access health services, you have to file tutelas," and "[e]verything happens through the tutela" (p. 359). In response to this perception, the Constitutional Court ruled that the tutela cannot be a required part of the process of obtaining health care in 2007 (C-950/07).…”
Section: Health and Housing In Colombiamentioning
confidence: 99%